2011
DOI: 10.1193/1.3587204
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of the ShakeOut Scenario

Abstract: For the ShakeOut Earthquake Scenario, we estimate $68 billion in direct and indirect business interruption (BI) and $11 billion in related costs in addition to the $113 billion in property damage in an eight-county Southern California region. The modeled conduits of shock to the economy are property damage and lifeline service outages that affect the economy's ability to produce. Property damage from fire is 50% greater than property damage from shaking because fire is more devastating. BI from water service d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…These models have proved versatile and accurate in their estimation of the total economic impacts of a range of hazards, including both terrorist attacks and natural disasters. Specific applications include the economic consequences of 9/11 (Rose and Blomberg 2010), a radiological dispersion device ("dirty bomb") attack (Giesecke et al 2012), an H1N1 epidemic (Dixon et al 2010), a major earthquake (Rose, Wei, and Wein 2011), and a severe winter storm and ensuing flooding (Sue Wing, Rose, and Wein 2010). Unfortunately, these models are time-consuming to construct and operate, and cannot provide quick response results unless a model for a specific region or country is already in place.…”
Section: Introductionmentioning
confidence: 99%
“…These models have proved versatile and accurate in their estimation of the total economic impacts of a range of hazards, including both terrorist attacks and natural disasters. Specific applications include the economic consequences of 9/11 (Rose and Blomberg 2010), a radiological dispersion device ("dirty bomb") attack (Giesecke et al 2012), an H1N1 epidemic (Dixon et al 2010), a major earthquake (Rose, Wei, and Wein 2011), and a severe winter storm and ensuing flooding (Sue Wing, Rose, and Wein 2010). Unfortunately, these models are time-consuming to construct and operate, and cannot provide quick response results unless a model for a specific region or country is already in place.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only the interdisciplinary articles cited recovery planning with any frequency, and most significantly, none of the practitioner articles cited this. However several articles on the outcomes of the Great Southern California ShakeOut indicated that planners advocated for more pre-event planning for postdisaster recovery (Rose 2011). In addition, several authors have documented the need for more recovery planning (Smith andWenger 2006, Berke andCampanella 2006) and the FEMA LTCR report highlights the need for both recovery planning and clear goals for the future during the recovery process (FEMA 2009).…”
Section: Community Resiliencementioning
confidence: 98%
“…Lifeline services may witness price increases, or, where subject to price regulation, may require rationing. Other key goods affecting the pace of recovery may be influenced, especially construction, in terms of a demand surge phenomenon …”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Estimates of property losses from Hurricane Katrina are nearly $100 billion, but BI losses now exceed $100 billion and counting because these losses just start at the time the disaster strikes and continue to rise until the regional economy has recovered to its predisaster trajectory or to a “new normal.” Total property damage (insured and uninsured) from the September 11, 2001 terrorist attacks on the World Trade Center is estimated at about $25 billion, but the consensus estimates of total BI losses are between $40 and $100 billion . Estimates of property damage from a hypothetical 8.2 Southern San Andreas Fault earthquake are $100 billion, with the associated BI losses at $67 billion . Typically, a larger proportion of property damage losses are insured than are the BI losses, but the market potential for the latter is enormous.…”
Section: Introductionmentioning
confidence: 99%